(1052) Structural Changes of the Egyptian Industry التغيرات الهيكلية في الصناعة المصرية - Hassan Abdel-Aziz Hassan. (INP, 2024)
The study explores the development of the industrial sector in a specific country during the 20th and early 21st centuries, emphasizing the policies impacting it post-1952. It divides the analysis into key periods, including rapid growth and structural shifts. The study examines the industrial sector's role in employment absorption and regional distribution, analyzes productivity trends, and assesses its relationship with other economic variables. It also discusses the sector's capacity to meet domestic needs and enhance exports. Finally, the study provides recommendations to optimize the industrial structure for sustainable development